Cannabidiol (CBD) Induces Functional Tregs in Response to Low-Level T Cell Activation - Dhital, Saphala (Cell Immunol, 2016)
Many effects of the non-psychoactive cannabinoid, cannabidiol (CBD), have been described in immune responses induced by strong immunological stimuli. It has also been shown that CBD enhances IL-2 production in response to low-level T cell stimulation. Since IL-2, in combination with TGF-β1, are critical for Treg induction, we hypothesized that CBD would induce CD4(+)CD25(+)FOXP3(+) Tregs in response to low-level stimulation. Low-level T cell stimulation conditions were established based on minimal CD25 expression in CD4(+) cells using suboptimal PMA/Io (4 nM/0.05 μM, S/o), ultrasuboptimal PMA/Io (1 nM/0.0125 μM, Us/o) or soluble anti-CD3/28 (400-800 ng each, s3/28). CBD increased CD25(+)FOXP3(+) cells from CD4(+), CD4(+)CD25(+), and CD4(+)CD25(−) T cells, as well as in CD4(+) T cells derived from FOXP3-GFP mice. Most importantly, the Us/o + CBD-induced CD4(+)CD25(+) Tregs robustly suppressed responder T cell proliferation, demonstrating that the mechanism by which CBD is immunosuppressive under low-level T cell stimulation involves induction of functional Tregs.